Epidermal growth factor receptor-targeted immunomagnetic liposomes for circulating tumor cell enumeration in non-small cell lung cancer treated with epidermal growth factor receptor-tyrosine kinase inhibitors. (June 2019) - Cui, Shaohua; Ni, Yiqian; Zhao, Yizhuo; Li, Zonghai; Xiong, Liwen; Liu, Jun; Liang, Xiaofei; Jiang, Liyan
Highlights: Establishment of CTC enrichment system by antibody modified EGFR-ML in NSCLC is feasible. Lower CTC numbers at one month after EGFR-TKI was associated with partial response during treatment. Patients with lower CTC numbers at 3 month after EGFR-TKI achieved a longer progression-free survival. CTC enumeration by EGFR-ML may supplement RECIST in dynamically monitoring NSCLC patients' response to first-line EGFR-TKI. Abstract: Objectives: To establish a circulating tumor cell (CTC) enrichment system for non-small cell lung cancer (NSCLC) patients who received first-line treatment with epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (EGFR-TKI), using EGFR magnetic liposomes (EGFR-ML). Materials and methods: An inverted evaporation method was used to develop antibody modified EGFR-ML. Peripheral blood was collected from NSCLC patients who underwent first-line EGFR-TKI treatment for CTC enumeration. Results: Protein electrophoresis, magnetic saturation curve, and ultraviolet absorption spectrum showed successful incorporation of the EGFR antibody on the surface of the magnetic microspheres, and the development of EGFR-ML was ascertained based on cell morphology and particle size. Using EGFR-ML, CTC were successfully enriched from blood samples and were identified in 77.3% (99/128) of the cohort. When compared to the 21L858R variant, EGFR-19del showed lower CTC counts by EGFR-ML (CTCEGFR ). At one month after EGFR-TKI, a lower CTCEGFR was associated with partial response (PR) during treatment (CTCEGFR < 6 vs. ≥ 6/7.5 mL, 75% vs. 49%, P = 0.027). In addition, patients with a lower CTCEGFR at 3 months after EGFR-TKI achieved a longer progression-free survival (PFS) [CTCEGFR < 6 vs. ≥ 6/7.5 mL, 13 months vs. 10.4 months, HR = 2.4, P = 0.042]. CTCEGFR significantly increased at the time of RECIST-progressive disease (RECIST-PD). Representative cases showed that CTCEGFR might increase before and beyond RECIST-PD until no clinical benefit could be acquired from EGFR-TKI. Conclusion: We showed that establishing a CTC enrichment system by antibody modified EGFR-ML in NSCLC is feasible. CTC enumeration by EGFR-ML may have the potential to supplement RECIST in dynamically monitoring the response of NSCLC patients' to first-line EGFR-TKI.